Effects of the foot strike pattern on muscle activity and neuromuscular fatigue in downhill trail running - Giandolini, M.; Horvais, N.; Rossi, J.; Millet, G. Y.; Morin, J.-B.; Samozino, P. (Scandinavian Journal of Medicine & Science in Sports, 2017)
Minimizing musculo-skeletal damage and fatigue is considered paramount for performance in trail running. Our purposes were to investigate the effects of the foot strike pattern and its variability on (a) muscle activity during a downhill trail run and (b) immediate and delayed neuromuscular fatigue. Twenty-three runners performed a 6.5-km run (1264 m of negative elevation change). Electromyographic activity of lower-limb muscles was recorded continuously. Heel and metatarsal accelerations were recorded to identify the running technique. Peripheral and central fatigue was assessed in knee extensors (KE) and plantar flexors (PF) at Pre-, Post-, and 2 days post downhill run (Post2d). Anterior patterns were associated with (a) higher gastrocnemius lateralis activity and lower tibialis anterior and vastus lateralis activity during the run and (b) larger decreases in KE high-frequency stimulus-evoked torque Post and larger decrements in KE MVC Post2d. High patterns variability during the run was associated with (a) smaller decreases in KE Db100 Post and MVC Post2d and (b) smaller decreases in PF MVC Post and Post2d. Anterior patterns increase the severity of KE peripheral fatigue. However, high foot strike pattern variability during the run reduced acute and delayed neuromuscular fatigue in KE and PF.